Role of epigenetics in the development of childhood asthma. Issue 2 (April 2018) - Davidson, Elizabeth J.; Yang, Ivana V.
Abstract : Purpose of review: Epigenetic marks are emerging as mediators of genetics and the environment on complex disease phenotypes, including childhood asthma and allergy. Recent findings: Epigenome-wide association studies over the past year have added to the growing body of evidence supporting significant associations of epigenetic regulation of gene expression and asthma and allergy. Studies in children have identified signatures of eosinophils in peripheral blood, Th2 cell transcription factors and cytokines in peripheral blood mononuclear cells, and epithelial dysfunction in the respiratory epithelium. Importantly, studies at birth have begun to decipher the contribution of epigenetic marks to asthma inception. Few studies have also begun to address the contribution of genetics and the environment to these associations. Summary: Next generation of epigenome-wide association studies that will deal with confounders, study the influence of the genetics and environment, and incorporate multiple datasets to provide better interpretation of the findings are on the horizon. Identification of key epigenetic marks that are shaped by genetics and the environment, and impact transcription of specific genes will help us have a better understanding of etiology, heterogeneity and severity of asthma, and will also empower us to develop biologically driven therapeutics and biomarkers for secondary prevention of this disease.